First data on Pneumocystis jirovecii colonization in patients with respiratory diseases in North Lebanon. (July 2015) - Khalife, S.; Aliouat, E.M.; Aliouat-Denis, C.M.; Gantois, N.; Devos, P.; Mallat, H.; Dei-Cas, E.; Dabboussi, F.; Hamze, M.; Fréalle, E.
Abstract: Pneumocystis colonization may play a role in transmission and local inflammatory response. It was explored in patients with respiratory diseases in North Lebanon. Overall prevalence reached only 5.2% (95% CI 2.13–10.47) but it was higher (17.3%) in the subpopulation of patients with chronic obstructive pulmonary disease (COPD). COPD was the only factor associated with a significantly increased risk of colonization. mtLSU genotyping revealed predominance of genotype 2, identified in five patients (71.4%), including one patient who had co-infection with genotype 3. These first data in North Lebanon confirm Pneumocystis circulation among patients with respiratory diseases and the potential for transmission to immunocompromised patients.